Entrepreneurship - Sarimah Hanim Aman Shah; Lan, Cecilia Soon Teik (Oxford Fajar Polytechnic series, 2013)
This book builds on the excellent exposition of entrepreneurship in the previous editions which were based on the latest polytechnic syllabus in Malaysia